Polysemy and Homonymy in Semantic Interpretation - Elan Nuroctavia Purba; Bernieke Anggita Ristia Damanik (Yayasan Bayt Shufiya Nusantara, 2025)
This article aims to examine the phenomena of polysemy and homonymy as major sources of lexical ambiguity that pose significant challenges in meaning interpretation, both in human communication and computational systems. Employing a literature review method, this study analyzes theoretical frameworks and relevant linguistic data. The findings reveal that polysemy refers to a single word with multiple related meanings, while homonymy involves identical word forms with unrelated meanings. Both phenomena complicate semantic understanding, particularly in pragmatic contexts and natural language processing tasks. The study emphasizes that pragmatic influence and frequency effects are key factors in meaning resolution and disambiguation. These findings underscore the importance of developing more advanced semantic-pragmatic models and effective disambiguation strategies to enhance language comprehension and improve the performance of natural language processing applications in human-computer interaction.